Can the system of discrete vortices imitate a boundary layer? - Lipniacki, T. (Archives of Mechanics, 1997)
The problem of dissipative flow of superfluid due to the vortex interaction with the boundary is considered within the hydrodynamics approximation. The numerical simulations were applied to show that, when the boundary starts moving, the vortices pinned to microscopic surface irregularities can stretch. The array of the growing vortices give rise to the specific boundary layer, which in some aspects is similar to the boundary layer in viscous fluids.